Preclinical models of radiation-induced cardiac toxicity: Potential mechanisms and biomarkers - Dreyfuss, Alexandra D.; Velalopoulou, Anastasia; Avgousti, Harris; Bell, Brett I.; Verginadis, Ioannis I. (Frontiers in Oncology, 2022)
Radiation therapy (RT) is an important modality in cancer treatment with >50% of cancer patients undergoing RT for curative or palliative intent. In patients with breast, lung, and esophageal cancer, as well as mediastinal malignancies, incidental RT dose to heart or vascular structures has been linked to the development of Radiation-Induced Heart Disease (RIHD) which manifests as ischemic heart disease, cardiomyopathy, cardiac dysfunction, and heart failure. Despite the remarkable progress in the delivery of radiotherapy treatment, off-target cardiac toxicities are unavoidable. One of the best-studied pathological consequences of incidental exposure of the heart to RT is collagen deposition and fibrosis, leading to the development of radiation-induced myocardial fibrosis (RIMF). However, the pathogenesis of RIMF is still largely unknown. Moreover, there are no available clinical approaches to reverse RIMF once it occurs and it continues to impair the quality of life of long-term cancer survivors. Hence, there is an increasing need for more clinically relevant preclinical models to elucidate the molecular and cellular mechanisms involved in the development of RIMF. This review offers an insight into the existing preclinical models to study RIHD and the suggested mechanisms of RIMF, as well as available multi-modality treatments and outcomes. Moreover, we summarize the valuable detection methods of RIHD/RIMF, and the clinical use of sensitive radiographic and circulating biomarkers.